The Intercultural Approach Reflected by Cultural Entities that Promote English Teaching in Colombia: A Critical Discourse Analysis (2023)
Cultural exchanges triggered a growing concern about how interculturality should be approached in academic settings by promoting good coexistence among the communities involved. From a critical perspective, cultural interaction should be balanced to avoid one culture overshadowing another (Walsh, 2009). To appreciate whether critical intercultural practices are developed in Colombia, this qualitative study aims to characterize the intercultural approaches that are embedded in the semiotic elements presented on the web pages of cultural entities such as Colombo Americano (CA) and British Council (BC) through a Critical Discourse Analysis (CDA), the methodology proposed by Van Dijk (2000). In the process of analyzing these semiotic elements, researchers also implemented Gee’s toolbox (2011), and Fairclough's CDA model (Durmaz & Yoğun, 2022). The most important findings indicate that the CA reflect a relational interculturality whilst the BC a functional one in the discourse of their web pages. At the same time, it was found that these entities’ power over English teaching in Colombia influences the interculturality that they promote.This research is important to create awareness of how an inclination towards a determined intercultural approach impacts the role that every culture plays in an educational setting. Additionally, it invites to question how some entities introduce interculturality, what is its basis, and for what purposes it is implemented, to notice whether English teaching practices in Colombia are aligned to the cultural needs of this country.